2020
DOI: 10.1093/gigascience/giaa013
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of the agarwood tree Aquilaria sinensis (Lour.) Spreng: the first chromosome-level draft genome in the Thymelaeceae family

Abstract: Backgroud Aquilaria sinensis (Lour.) Spreng is one of the important plant resources involved in the production of agarwood in China. The agarwood resin collected from wounded Aquilaria trees has been used in Asia for aromatic or medicinal purposes from ancient times, although the mechanism underlying the formation of agarwood still remains poorly understood owing to a lack of accurate and high-quality genetic information. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 72 publications
1
44
0
Order By: Relevance
“…In particular, recursive polyploidization, polyploidization of different ploidy, and genome rearrangement have been observed in angiosperms [9,10]. As a valuable plant, the genome of A. sinensis has been sequenced by two independent groups [11,12]. It was reported that the genome of A. sinensis experienced a recent WGD event [11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recursive polyploidization, polyploidization of different ploidy, and genome rearrangement have been observed in angiosperms [9,10]. As a valuable plant, the genome of A. sinensis has been sequenced by two independent groups [11,12]. It was reported that the genome of A. sinensis experienced a recent WGD event [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thailand (Ding et al 2020). It is one of the most important plant species for producing agarwood, and A. sinensis material has long been used as a sedative, digestive and anti-emetic drug in traditional medicine and as unique perfume and incense (Ding et al 2020;Xu et al 2020 The AsTal1 cDNA sequence containing class-speci c TAL conserved domains and nucleotide sequences was obtained from the A. sinensis callus transcriptomic dataset. To isolate this gene from A. sinensis calli, open reading frames (ORFs) were isolated via RT-PCR using speci c primers ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Hi-C technology has emerged as a robust tool to reconstruct genomes at the chromosome level, providing long-range information about the grouping and linear organization of sequences along entire chromosomes ( Burton et al 2013 ). Recently, several high-quality plant genomes had been obtained by using Nanopore sequencing and Hi-C technologies, including Eriobotrya japonica ( Jiang et al 2020 ), Aquilaria sinensis ( Ding et al 2020 ), and Asparagus setaceus ( Li et al 2020 ).…”
mentioning
confidence: 99%